HEALTH SCREENING FOR TEACHERS OF MADRASAH IBITIDAIYAH 2 AL KHOIRIYYAH GARUT - N. Ai Erlinawati , N. Ai Erlinawati; Muhammad Hadi Sulhan, Muhammad Hadi Sulhan; Tantri Puspita, Tantri Puspita; Gina Nafsa Mutmainna, Gina Nafsa Mutmainna; Aceng Ali Awaludin, Aceng Ali Awaludin (LP4M STIKes Karsa Husada Garut, 2024)
Health checks are essential for teachers to ensure that they remain healthy and can carry out their teaching duties properly. Both physical and mental health conditions are very influential on the health conditions of students so it is very important that teachers' health is checked regularly. The purpose of implementing this community service activity is to explore teacher health information. The implementation method used is by measuring blood pressure, saturation and body temperature and conducting health counseling with lectures and discussions. The results obtained showed that most of the teachers' blood pressure was normal, oxygen saturation was normal and body temperature was normal. The conclusion of this activity is that the health condition status of teachers in MI 2 is normal and healthy.